Research on function and mechanisms of a novel small molecule WG449E for hypertrophic scar. (11th December 2019) - Shao, T.; Tang, W.; Li, Y.; Gao, D.; Lv, K.; He, P.; Song, Y.; Gao, S.; Liu, M.; Chen, Y.; Yi, Z.
Abstract: Background: Hypertrophic scars are complications of severe wound healing characterized by excessive fibrosis associated with aberrant function of fibroblasts. However, no available drugs can be utilized to effectively treat these scars. The transforming growth factor β (TGFβ) signalling pathway regulates collagen synthesis and plays an important role in scar formation. Objectives: To evaluate the anti‐scar effects of TGFβ inhibitors in vitro and in vivo . Methods: Col1α2‐luciferase reporter assay was used to screen the compounds suppress type I collagen gene transcription. Sulforhodamine B colorimetric assay and colony formation assay were used to test the compound's effect on cell proliferation. Wound healing and transwell assay were performed to test the cell migration and invasion. Western blotting, immunofluorescence, immunohistochemistry and Q‐PCR assay were used to determine the protein and mRNA levels. 3D cell contraction assay was used to examine the cell contraction. Flow cytometry was performed to analyse cell apoptosis. Masson stain, H&E stain and immunochemistry were used to analyse the scar formation in vivo . Results: WG449E, as one of the most potent inhibitors, was identified to significantly downregulate the mRNA and protein levels of collagen in hypertrophic scar‐derived fibroblasts through inhibiting Smad2/3 phosphorylation. WG449E inhibited the proliferation, migration and contraction of fibroblasts in vitro and in vivo . In addition, WG449E induced cell apoptosis through the activation of cleaved‐caspase3. Moreover, WG449E significantly attenuated hypertrophic scar formation and collagen deposition in a mechanical load‐induced mouse model. Conclusions: WG449E is a potential candidate for the treatment of hypertrophic scars.WG449E downregulates the mRNA and protein levels of collagen in hypertrophic scar‐derived fibroblasts through inhibiting Smad2/3 phosphorylation and nucleic localization. WG449E blocks HSF migration and invasion by regulating F‐actin assignment. In addition, WG449E induces HSF apoptosis through the activation of cleaved‐caspase3.